Amplified binding-induced homogeneous assay through catalytic cycling of analyte for ultrasensitive protein detection. Issue 9 (15th December 2015) - Chen, Junbo; Deng, Bin; Wu, Peng; Li, Feng; Li, Xing-Fang; Le, X. Chris; Zhang, Hongquan; Hou, Xiandeng
Abstract : Amplified binding-induced homogeneous assay through catalytic cycling of analytes for ultrasensitive protein detection. Abstract : By using the principle of binding-induced DNA assembly, we have developed a novel homogeneous assay that is able to convert an affinity protein binding event into a predesigned DNA assembly. The assembled DNA sequence can be ligated into an intact DNA strand and hundreds of DNA hairpins can be cleaved by a nicking endonuclease. Each cleavage releases a single-stranded DNA (ssDNA) probe that is initially caged in the DNA hairpin. This released ssDNA probe can then turn on the fluorescence signal by desorbing a fluorescently-labelled complementary DNA probe from graphene oxide through hybridization. We demonstrate that this homogeneous, isothermal, and amplifiable assay can be tailored to detect a number of proteins, including a cancer biomarker, human prostate specific antigen, at picomolar levels in both buffer and human serum samples.